The vet my wild and wonderful friends - Gamble, Luke (Two Roads, an imprint of Hodder & Stoughton, 2011)
Fresh out of university Luke joins a mixed practice in Dorset, run by the stern but benevolent Mr Spotswode and is quickly thrust into the real world of veterinary medicine. Luke's dream is to set up on his own and find his place in the world. These things, however, are never quite straightforward.